1996
DOI: 10.1074/jbc.271.19.11362
|View full text |Cite
|
Sign up to set email alerts
|

Inter-α-trypsin Inhibitor Bound to Tumor Cells Is Cleaved into the Heavy Chains and the Light Chain on the Cell Surface

Abstract: Inter-␣-trypsin inhibitor (ITI),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…Similar results were also obtained upon incubation of I␣I with tumor cells (40). Whether this cleavage process is of physiological significance remains to be seen.…”
Section: Fig 5 Partial Proteolytic Degradation Of H2supporting
confidence: 76%
“…Similar results were also obtained upon incubation of I␣I with tumor cells (40). Whether this cleavage process is of physiological significance remains to be seen.…”
Section: Fig 5 Partial Proteolytic Degradation Of H2supporting
confidence: 76%
“…We have previously shown that in human umbilical vein endothelial cells and promyeloid leukemia cell line U937 activation of PKC represents a critical event in tumor necrosis factor-triggered signaling cascade leading to uPA secretion (12). Furthermore, we had shown that induction of uPA expression by tumor necrosis factor-␣ was inhibited when these cells were incubated with UTI and that UTI may influence the PKC-dependent protein kinase pathway in uPA expression.…”
Section: Uti Suppresses Pma-triggered Phosphorylation Of Mek1 Erk2mentioning
confidence: 95%
“…Agents that modulate uPA have been shown to alter the rate of metastasis in in vitro experiments and in some animal models (16). Recent publication demonstrated that UTI with anti-inflammatory and anti-tumor promoting properties can influence the PKC-dependent signal pathway in uPA expression in cultured human umbilical vein endothelial cells and in the promyeloid leukemia cell line U937 (12); exogenous UTI inhibits a rapid increase in membrane-associated PKC activity, and a decrease in cytosolic PKC activity. However, the precise molecular mechanisms of the UTI-mediated changes occurring downstream of the PKC signal transduction have remained unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this system, it is clear that HA is the major structural component that determines the viscoelastic properties of the expanding matrix of the cumulus-oophorus. It is well established that members of the I␣I family are pivotal for the formation of the cell-oocyte complexes matrix, where covalent linkage of HC of I␣I (HC1 and HC2) and P␣I (HC3) to HA has been demonstrated (26,27), an interaction that has been postulated to contribute to the stabilization of the ECM (28,29). More recent studies suggest that I␣I components are associated with HA-based cables on colonic smooth muscle cells (30).…”
mentioning
confidence: 99%